Faktor-Faktor yang Mempengaruhi Keputusan Petani Padi Memilih Kredit di Bank (Studi Kasus Kecamatan Wonomulyo Kabupaten Polewali Mandar) - Ikram, I; Yusuf, Syarifuddin; Abdullah B, A (Journal Galung Tropika, 2020)
This study aims to determine and analyze the influence of partially and the influence together with farmers' income, interest rates, loan amount, credit repayment period, credit distribution process, collateral/credit, and credit services to the decision of rice farmers to choose credit at the bank. The population in this study were rice farmers who took credit at the bank, both those who were still active in a credit or had paid off who were domiciled and were members of farmer groups in Wonomulyo District, Polewali Mandar Regency, West Sulawesi Province. Data were analyzed using multiple linear regression analysis and coefficient of determination. The results showed that the farmers' income partially had a negative and significant effect on the decision of rice farmers to choose credit at the bank. The amount of credit and credit services has a positive and significant effect on the decision of rice farmers to choose credit at the bank. The interest rate, repayment period, credit distribution process, and collateral/collateral do not significantly influence the decision of rice farmers to choose credit at the bank. Farmers' income influences the decision of rice farmers to choose credit at the bank.